Nothing Like Chocolate - Bhavnani, Kum-Kum (United States, 2012)
The film traces the continued growth of Mott’s co-operative, exposing the practices and politics of how chocolate has moved worldwide from a sacred plant to corporate blasphemy.
Soros Documentary Fund
Keywords: Documentary films